(untitled) (REVISTA NODO, 2015)
This research aims to determine possible relationships between the end deficient or inadequate disposal of solid waste and damage to human health. Each identifies and warns about the problems of environmental degradation through pollution and harmful health consequences and possible diseases to which they are exposed due to poor management of solid and liquid wastes This ocurrs in the educational community school Los Toldos in the city of Popayan, Cauca.